Targeting the circadian modulation: novel therapeutic approaches in the management of ASD - Zhang, Yuxing; Chen, Yinan; Li, Wu; Tang, Liya; Li, Jiangshan; Feng, Xiang (Frontiers in Psychiatry, 2024)
Circadian dysfunction is prevalent in neurodevelopmental disorders, particularly in autism spectrum disorder (ASD). A plethora of empirical studies demonstrate a strong correlation between ASD and circadian disruption, suggesting that modulation of circadian rhythms and the clocks could yield satisfactory advancements. Research indicates that circadian dysfunction associated with abnormal neurodevelopmental phenotypes in ASD individuals, potentially contribute to synapse plasticity disruption. Therefore, targeting circadian rhythms may emerge as a key therapeutic approach. In this study, we did a brief review of the mammalian circadian clock, and the correlation between the circadian mechanism and the pathology of ASD at multiple levels. In addition, we highlight that circadian is the target or modulator to participate in the therapeutic approaches in the management of ASD, such as phototherapy, melatonin, modulating circadian components, natural compounds, and chronotherapies. A deep understanding of the circadian clock's regulatory role in the neurodevelopmental phenotypes in ASD may inspire novel strategies for improving ASD treatment.